(untitled) (Bangladesh Medical Journal, 2021)
Diagnosis of congenital heart disease (CHD) which is a structural abnormality of the heart or intra thoracic great vessels in the earliest possible time is very important. Identifying the various modes of presentation, early referral and appropriate intervention can save lives and reduce risk of complications. The objectives of this study were to determine the clinical profile, complication and immediate outcome of children with congenital heart disease in first year of life. This cross-sectional observational study was conducted from October 2011 to March 2012 among 50 children from zero to one year of age who was diagnosed as CHD by echocardiography admitted in Department of Paediatrics of ShaheedSuhrawardy Medical College, Dhaka and Department of Paediatric Cardiology of National Institute of Cardiovascular Diseases, Dhaka, Bangladesh. Among 50 infants acyanotic CHD was detected in 70% and cyanotic in 30% infants. Major structural defects were venticularseptal defect 34%, patent ductusarteriosus 30%, tetralogy of fallot’s 14%, transposition of great arteries 12%, atrial septal defect 6%. Presenting features were cough 82%, dyspnea 80%, poor weight gain 70%, feeding difficulty 68% and fever 58%. Frequently observed complications were failure to thrive, pulmonary hypertension and heart failure. Among the outcome of CHD 8% cases closed spontaneously, case fatality rate was 8% and the rest were advised accordingly for surgery, intervention and medical management among which 14% had device closure within the study period. High index of suspicion, early diagnosis, close monitoring and timely intervention can reduce complication of CHD. Bangladesh Med J. 2020 Sept; 49(3) : 17-21